Uterine Arteriovenous Malformation - Oguz, Yuksel; Eldem, Fatma Gonca; Cil, Barbaros; Sanhal, Cem; Gencosmanoglu Turkmen, Gulenay; Yucel, Aykan; Uygur, Dilek (Gynecology Obstetrics & Reproductive Medicine, 2019)
We aimed to report a case of uterine arteriovenous malformation (UAVM) which was successfully treated by uterine artery embolization. A multiparous 23-year-old woman referred to our clinic for 7 weeks scar pregnancy. On ultrasound, incisional 32×37 mm gestational sac surrounded with non-pulsatile high flow vessels was demonstrated. Uterine artery embolization was performed with Gelfoam by interventional radiology. The post-embolization arteriogram showed complete embolization of the UAVM with slow flow of contrast in both uterine arteries. In clinical suspicion, UAVM can be diagnosed with Doppler ultrasonography and can be treated successfully with either uterine artery embolization or uterine surgery. UAVM is commonly diagnosed in women of childbearing age, angiographic embolization should be the firstly preferred treatment.